2020
DOI: 10.1128/jcm.00776-20
|View full text |Cite
|
Sign up to set email alerts
|

Saliva as a Noninvasive Specimen for Detection of SARS-CoV-2

Abstract: 12Diagnostic testing for COVID-19 is central to controlling the global pandemic. Recently, To and 13 colleagues reported that 20 of 23 (87%) patients who had SARS-CoV-2 detected by reverse-14 transcriptase PCR (RT-PCR) in nasopharyngeal swabs (NPS) or sputum also had SARS-CoV-2 15 detectable in saliva (1). The use of saliva has several advantages compared to collection of NPS. In 16 particular, the close contact involved in swab collection poses a risk to healthcare workers, and 17 collection of saliva may red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
465
6
20

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 383 publications
(527 citation statements)
references
References 5 publications
28
465
6
20
Order By: Relevance
“…In this study, only 84.9% of NPS samples were confirmed with saliva. This reduced sensitivity seems to be related to reduced viral titer in saliva samples [12] as well as differences in temporal dynamics in shedding in upper respiratory locations versus saliva [13,14] . Lastly, in convalescent patients, viral titers remain at detectable levels up to 21 days after initial testing [15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only 84.9% of NPS samples were confirmed with saliva. This reduced sensitivity seems to be related to reduced viral titer in saliva samples [12] as well as differences in temporal dynamics in shedding in upper respiratory locations versus saliva [13,14] . Lastly, in convalescent patients, viral titers remain at detectable levels up to 21 days after initial testing [15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…The WHO currently recommends RT-PCR testing using nasopharyngeal (NPS) and oropharyngeal swabs (OPS) as gold standard for SARS-CoV-2 diagnosis and for monitoring viral load [ 4 , 5 ]. OF has been suggested as an alternate clinical sample, easy and safer to collect, minimizing exposure of healthcare workers and could be useful for making a diagnosis and measuring SARS-CoV-2 viral load and viral shedding during the course of the illness and convalescence [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. To et al, demonstrated that SARS-CoV-2 was present in OF specimen of 11 out of 12 patients, with viral load being higher during the first week after symptoms onset and declining thereafter, being detectable until 25 days after symptoms onset (DSO) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-collecting saliva specimens are noninvasive tool for the virus detection and reduce a risk of health care workers. A series of recent studies have shown efficacy of saliva as a diagnostic tool(6-10). We recently reported 97% concordance rate between nasopharyngeal swab samples and saliva in the detection of SARS-CoV-2(11).…”
Section: Introductionmentioning
confidence: 99%